Partisipasi Guru Sekolah Tingkat Dasar Dalam Sanggar Seni Karawitan Sekar Madu Pada Pembelajaran Seni Budaya dan Prakarya - Hartono Hartono; Abdur Rahim; Anjar Sulistyani (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
Karawitan is an art work living, surviving and developing in Java, Indonesia. It has a very important function in people's lives. From the Karawitan learning activities at the art group of “Seni Karawitan Sekar Madu”, it is expected to promote and increase students interest to love the culture of Indonesia through the implementation of Cultural Arts and Crafts lesson. This study aims to describe: (1) the practice of Karawitan musical art training by elementary school teachers (2) implementation of cultural arts and crafts lesson (3) supporting and inhibiting factors of Karawitan musical learning at